Treatment of aggressive pituitary tumours and carcinomas: results of a European Society of Endocrinology (ESE) survey 2016. Issue 3 (March 2018) - McCormack, Ann; Dekkers, Olaf M; Petersenn, Stephan; Popovic, Vera; Trouillas, Jacqueline; Raverot, Gerald; Burman, Pia; ,
Abstract : Objective: To collect outcome data in a large cohort of patients with aggressive pituitary tumours (APT)/carcinomas (PC) and specifically report effects of temozolomide (TMZ) treatment. Design: Electronic survey to ESE members Dec 2015–Nov 2016. Results: Reports on 166 patients (40 PC, 125 APT, 1 unclassified) were obtained. Median age at diagnosis was 43 (range 4–79) years. 69% of the tumours were clinically functioning, and the most frequent immunohistochemical subtype were corticotroph tumours (45%). Ki-67 index did not distinguish APT from PC, median 7% and 10% respectively. TMZ was first-line chemotherapy in 157 patients. At the end of the treatment (median 9 cycles), radiological evaluation showed complete response (CR) in 6%, partial response (PR) in 31%, stable disease (SD) in 33% and progressive disease in 30%. Response was more frequent in patients receiving concomitant radiotherapy and TMZ. CR was seen only in patients with low MGMT expression. Clinically functioning tumours were more likely to respond than non-functioning tumours, independent of MGMT status. Of patients with CR, PR and SD, 25, 40 and 48% respectively progressed after a median of 12-month follow-up. Other oncological drugs given as primary treatment and to TMZ failures resulted in PR in 20%. Conclusion: This survey confirms that TMZ is established as first-line chemotherapeutic treatment of APT/PC. Clinically functioning tumours, low MGMT and concurrent radiotherapy were associated with a better response. The limited long-term effect of TMZ and the poor efficacy of other drugs highlight the need to identify additional effective therapies.